2022
DOI: 10.3390/ijerph20010518
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Furr-Recovery Method: Interacting with Pets in Teleworking Replenishes the Self’s Regulatory Resources: Evidence from a Daily-Diary Study

Abstract: This study is based on the conservation of resources theory and the recovery step model in order to further explore the furr-recovery method—a mechanism through which workers break their routine by taking micro-moments to interact with their “furry co-workers,” thus relieving their fatigue and tension or other negative affective states. Based on this, we argue that this method not only serves the purpose of restoring self-regulatory resources but also ameliorates mental health. Accordingly, this study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…In addition, it would be useful to consider the type of pet and the level of emotional attachment as moderators within the AET framework. At last, because this study only considers pet ownership, and there is evidence of the beneficial effects of human-animal interactions for a wide range of work and personal outcomes (see Junça-Silva, 2023c), future studies should consider testing the model with human-animal interactions as a moderator.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it would be useful to consider the type of pet and the level of emotional attachment as moderators within the AET framework. At last, because this study only considers pet ownership, and there is evidence of the beneficial effects of human-animal interactions for a wide range of work and personal outcomes (see Junça-Silva, 2023c), future studies should consider testing the model with human-animal interactions as a moderator.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…The beneficial effects of working near pets may be supported by the literature (e.g., Junça-Silva, 2023b). Recently, some studies have shown that workers who own pets and work from home have increased performance rates (Wagner & Pina e Cunha, 2021), are more engaged with their work (Sousa et al, 2022), and feel happier (Junça-Silva, 2023c). Thus, workers who own pets if they are allowed to work from home, even hybrid, may feel a greater sense of obligation and commitment to their employer, which may be translated into higher well-being, gratitude, and happiness (Junça-Silva et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The lack of direct interactions disconnects the employee from relevant information and/or rapid identification of opportunities in professional development. The COVID-19 pandemic also contributed to less face-to-face interaction between colleagues, leading to the need to develop other interactions in order to supply the micro-breaks that help an employee relax [74]. The COVID-19 pandemic context also increased the need of teleworking employees to have constant communication with colleagues and supervisors, as this interaction significantly influenced their well-being [51].…”
Section: Hypothesis 3 (H3) Teleworking Influences the Insecurity Of C...mentioning
confidence: 99%
“…Recently, Junça-Silva [ 11 , 12 ] demonstrated that human-animal interactions in the work context not only relaxed employees but created moments for them to recover and respite – the furr-recovery method. Accordingly, interacting with pets (e.g., petting the dog’s head) during work time may be a micro-break that distracts employees from work and helps them recover self-regulatory resources that are needed for them to deal with daily hassles.…”
Section: The Mediating Role Of Perceived Uncertaintymentioning
confidence: 99%
“…Relying on the “furr-recovery method” [ 11 , 12 ], I argue that dog owners will react differently to daily hassles when compared to employees who do not own dogs. The furr-recovery method explains that interacting with a pet during work time will serve as a micro-break that restores lost energy, stamina, and motivation, making the individual ready to invest additional efforts in their work [ 11 , 12 ]. Hence, based on this, we expect that those who own dogs will deal with daily hassles differently from those who do not own dogs.…”
Section: Introductionmentioning
confidence: 99%